VISION OF DEATH IN EDGAR ALLAN POE’S SELECTED POEM (Archive of Conferences, 2021)
Poetry is greatly influenced by the cultural background and personal experiences of the poets. In this paper I shall approach to personify of allegorical Death in art and literature. "The Conqueror Worm" poem tells the allegorical history of mankind. The work acts as a frame story, where the outside frame is that of a throng of angels watching a play, and the inside frame is that of the play itself. The narrative poem, also contains a typical plot construction. The first stanza serves as the exposition, placing the angels at night in the setting of a theatre, while the second and third stanzas provide the rising action. The climax comes with the entrance and triumph of the Conqueror Worm, and the last stanza returns to the outside frame for the falling action and denouement.